Power durability measurement of radio frequency surface acoustic wave and bulk acoustic wave devices taking the influence of their temperature dependences into account. (4th June 2018) - Qiu, Luyan; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: In this paper, we describe the study of time to failure (TTF) evaluation of radio frequency (RF) surface and bulk acoustic wave (SAW/BAW) devices for the International Electrotechnical Commission (IEC) standardization. As the passband shifts with T due to the nonzero temperature coefficient of frequency (TCF), its influence must be taken into account at the acceleration test. A technique to estimate the frequency-dependent TCF of RF SAW/BAW devices for the acceleration test of the TTF estimation is proposed. First, it is shown how the filter passband shifts with T, and its numerical model is proposed. Then, its impact on the power durability test is presented.